The State of Blood Transport Systеms and the Immune System in Apparently Healthy Residents of the European North of Russia (Arkhangelsk Region) - Kseniya O. Pashinskaya (Northern (Arctic) Federal University, 2024)
Adaptive restructuring gets disrupted due to a reduction in the body's reserve capacity at increased stress on the functional systems in response to the combined effects of adverse factors, including climatic. Determination of the state of blood transport systems and immune homeostasis broadens our understanding of how human body systems operate under adverse conditions of the North. The purpose of this article was to assess the state of the transport components of the blood system in relation to the immune status of the population of the European North of Russia. Materials and methods. A survey of 789 residents of the Arkhangelsk Region aged 21 to 55 years was conducted and their blood system parameters were analysed taking into account the levels of haptoglobin, transferrin, immunoglobulins and lipid transport complexes with their structural ligands. Results. Residents of the European North of Russia showed increased levels of transferrin in 31.8 %, IgM in 7.6 %, IgE in 7.8 % and low-density lipoproteins in 10.2 % of cases, as well as a deficit in IgA in 55.6 % and high-density lipoprotein apoA-I ligand in 56.2 % of cases. Elevated blood transferrin concentrations are associated with low CD71+ lymphocyte count, which reflects the inhibition of activation and proliferation processes when the signal from the CD3+ receptor is blocked. A decrease in the level of transferrin CD71+ receptors on lymphocytes is manifested in disturbed immunoglobulin class switching with the formation of IgA deficit, which is compensated by IgM and IgE. Increased immunoglobulin content ensures effective binding of metabolic products with autoantigen properties (low-density lipoproteins) when the functional properties of high-density lipoproteins are impaired due to the structural apoA-I deficit. Determination of the transport components of the blood system in relation to the state of the immune system is informative for assessing the risk of disruption of adaptive mechanisms.